Primary and secondary lithic raw material sources along the western coast of San Matías Gulf (Río Negro province, Argentina): A first approach to their spatial variability - Alberti, Jimena (2015)
In this article we present a first description of lithic raw material sources, and their particular geological and geomorphological characteristics, from the south part of the western coast of San Matías Gulf. The study area lineally covers ~125 km of the west coast of Río Negro province, Patagonia, Argentina (from 404803.2200S, 654015.7700W to 4155043.6000S, 653050.1500W). The sources uncovered include concentrations of different types of shingle to primary outcrop, which is an exceptional find considering that to date all known sources along the western and the northern coasts of the Gulf were secondary. As a result we now know about a considerable number of rock types of varying quality for knapping, as well as their differential distribution across space. This allows us, for the first time in our study area, to study procurement and exploitation strategies for these raw materials and also to briefly discuss the existing contrasts in rock availability across different sectors of space. The results of these studies suggest that the differential representation of these rocks in the archaeological record across space was related to variations in their spatial and temporal availability, which in turn was tied to the very formation process of the coastal archaeological record of this north Patagonian area.